The Study of Interest in English for Communication and Tourism in the Local of the High School Students in the Area of Pataem National Park in Kongchiam District of Ubon Ratchathani Province - Chaisena, Assoc. Prof. Dr. Malee; Chaisena, Assoc. Prof. Dr. Phod (Journal for Developing the Social and Community, 2018)
The research aimed to study of interest in English for communication and tourism in the Local of the high school students in the area of Pataem National Park in Kongchiam district of Ubon Ratchathani province. The target groups used in the study were the high school students in the area of the Pataem National Park for 130 student. The research instruments were a questionnaire. Statistics used in data analysis were percentage. The research findings were as follows: The majority of the students had an interest in 11 topic. Their needs were found in the following: (1) history of Kongchiam district, (2) indigenous people, (3) location and boundary, (4) Pataem painting, (5) ancient painting, (6) rituals, (7) the Candle Festival, (8) folk performance locally known as ‘Morlum’, (9) basketry, (10) green papaya salad, and (11) the ways to describe the directions.